Risk versus reward: Interactions, depredation rates, and bycatch mitigation of dolphins in demersal fish trawls - Santana Garcon, Julia; Wakefield, Corey; Dorman, S.; Denham, A.; Blight, S.; Molony, B.; Newman, Stephen (NRC Research Press, 2018)
© 2018, Canadian Science Publishing. All rights reserved. An improved understanding of interaction dynamics between dolphins and trawlers is essential for improving bycatch mitigation strategies. In-situ observations using video at increasing distances from the net opening during 50 commercial fish trawls, recorded 5908 common bottlenose dolphin (Tursiops truncatus (Montagu, 1821)) interactions and provided details on their duration, depredation rates, and behaviours. Dolphin interactions with trawls were very common (98% of day-trawls, 118 ± 16 interactions per trawl), with durations and prey consumption positively correlated with the distances ventured into the net. Acoustic deterrents (pingers) had no effect on interaction numbers or durations. Based on in-situ observations, the factors that contribute toward dolphin bycatch in demersal fish trawls were likely associated with (i) risky dolphin behaviour (i.e., entering net during hauling, residing deep within trawl for extended periods or social aggression) and (or) (ii) instability of fishing gear resulting in entrapment. Given the high level of dolphin attendance during most day-trawls, mitigation strategies that focus on improving and monitoring the stability of trawl gear would be more effective than current acoustic deterrent devices aimed at modifying dolphin behaviour.